In vitro study about the abutment axial wall's convergence - Cerghizan Diana; Crăciun Adriana; Albu Aurița; Baloș Monica; Jánosi Kinga Mária ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
Introduction: The total convergence of the axial walls is the angle made between the opposing axial walls of an abutment. The lower the taper value, the better the retention of the crowns is. Obtaining a proper convergence of the axial wall is a challenge for dental practitioners due to limited access and low visibility, but it also greatly depends on the clinician's practical skills.